The Big Five dimensions of individual differences in personality - Laak, Jan J. F. ter (1996)
This is a review anide about the different theoretical positions on the Big Five dimensions of personality . This article presents the similarities and dilferences among the theoretical positions following a thorough reflection on the following topics: (a) the genesis of the content and structure of the Big Five; (b) the robustness of the five dimensions; (e) a description of the research on the relationship of the Big Five with other personality constructs; (d) a di~cussion about the predictive value of the Big Five profile scores for relevant criteria; (e) the theoretical status of the Five is analyzed; (f) historical criticisms on the Big Five are discussed; (g) sorne guesses for the future of the Five are put forward; and (h) conclusions and remarks about the Five dimensions of personality are drawn and made.